Is the diagnosis and treatment of childhood acute bacterial meningitis in Turkey evidence-based? - (:unkn) unknown (My University, 2014)
0

Background/aim: Evidence-based guidance is likely to significantly improve patient care. We aimed to characterize the adequacy of standard diagnostic methods and treatment in children with acute bacterial meningitis (ABM) in Turkey. Materials and methods: We conducted a retrospective study among children 1 month to 5 years old hospitalized with ABM in İstanbul. The World Health Organization case definition and laboratory criteria were used for diagnosis. Results: Of the 283 cases, 250 were probable and 33 (11.2%) were confirmed as bacterial meningitis. The majority of patients (92%) were treated at 9 governmental hospitals and the remaining 21 at 2 university hospitals. Blood culture, cerebrospinal fluid (CSF) culture, and CSF Gram smear examinations were performed in 68%, 87%, and 13% of the cases, respectively. A third-generation cephalosporin, alone or in combination with other antibiotics, was the drug of choice in 90% of cases. Dexamethasone was given as adjunctive therapy in 43%. Initial antibiotics were modified during the course of treatment for 43 patients, with culture-confirmed indications for only 5 of them. Conclusion: Recommended laboratory tests including blood culture and CSF Gram smears were insufficiently performed. Appropriate antibiotics were used in the majority of cases. Better identification of the causative pathogens will improve stewardship of antimicrobial therapy
Keywords: Cerrahi